Corak Maqashidi dalam Tafsir Alquran - Hamdani Anwar (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2017)
Maqashidi is a theory that contains the values and goals which the aim of Allah rules is derived. The theory which is an im- portant part of the study of the science of Ushul fiqh, is also devel- oped in the Qur’anic commentary, so its interpretation based on the purpose of establishing the Shari’a (maqashid asy-syari’ah), has been able to produce a contextual interpretation, exposing the universal meaning of the Qur’an and minimize the dissent that always exists in interpretation. The Attempts in aligning the information from the Qur’an with the purpose of the Shari’a (maqashid asy-syari’ah) like this is a worth appreciation activity, given the function of the Qur’an as a guide for the welfare of humanity. This paper introduces the in- terpretation of Maqashidi which is expected to provide understand- ing to the Muslims of the importance of tafsir maqasidi at this time.